Morphological shell variation of Zidona dufresnei (Caenogastropoda: Volutidae) from the Southwestern Atlantic Ocean - Medina, Alonso Ismael (2020)
The volutid gastropod Zidona dufresnei is an important fishery resource from the Southwestern Atlantic Ocean. This species exhibits strong interpopulation differences in life history features, which lead to postulate the existence of two morphotype ('normal' and 'dwarf'). In this study, we combine and compare traditional and geometric morphometrics to capture shell shape variation of Z. dufresnei among three populations from Mar del Plata (37° S) to San Matías Gulf (42° S) to test the hypothesis that the phenotypic variation already described in the life cycle and size is also expressed in the shell shape. Significant differences in the shell morphology among these three populations were detected, mainly associated to the maximum size of individuals and shell shape. The Bahía San Antonio morphotype had shells with higher general roundness and weight compared to San Matías Gulf and Mar del Plata morphotypes, which were not differentiated. Our results support the hypothesis of Lahille (1895) who distinguished the morphotype of Bahía San Antonio ('dwarf' morphotype) as Voluta angulata affinis. The functional significance of the variability found is discussed in terms of the ecological and genetic effects on shape and size.